Analisis Strategi Bisnis Build, Borrow, & Buy Pt Telkom Indonesia, Tbk - Ginanjar, Jajang; Hermanto, Bambang; Herawati, Tetty (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
This paper examines the implementation of Laurence Capron’s business strategies Build, Borrow, and Buy at PT Telkom Indonesia, Tbk. Identify how relevant it is to the Covid-19 pandemic condition, then analyzed through the perspective of technological and social change. The research’s using qualitative methods through literature review by collecting data from previous research. The results show that PT Telkom Indonesia, Tbk has successfully implemented the Build, Borrow, and Buy strategies in its business operations and maintain company sustainability during the pandemic, technological and social changes related to the implementation of the Build, Borrow, and Buy strategy. The implications of this research are the Build, Borrow, and Buy strategy analysis can be a reference to be applied to other entities, and can be linked to different variables or perspectives with a more focused and stay relevant so that depth of analysis can be achieved.